IMPLEMENTASI PENDAFTARAN HAK ATAS TANAH SECARA SISTEMATIK MELALUI PROYEK AJUDIKASI DI KUBAR - Roni Vintcen Manalu (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACT The registration of land rights through the Adjudication project in Kubar, in practice, is not complicated and the registration is easy. Where the location has been determined based on criteria in the decision of the Minister of Agrarian Affairs No. 3 of 1995 where the location of the evidence is still little or not much land has been registered by the owner, the registration of land through this adjudication is more effective than the sporadic land registration carried out by the landowners themselves. a target of 10,000 plots because in Kubar from land registration through the Adjudication project in accordance with Government Regulation No.24 of 1997 and Article 19 of the Logga it has been achieved that there is legal certainty from each of them with a certificate as evidence. In the implementation of registration through the adjudication project is inseparable from the factors that support the cheap registration fee of only Rp. 13,500.00 and registrants do not need to go back and forth to administer the administration, and the registration requirements are easy so that the implementation is easier to carry out. inhibiting factors for the systematic registration of land rights through an adjudication project can be overcome so that the implementation runs smoothly in accordance with the objectives of Government Regulation No.24 of 1997 concerning the need for land registration. Keywords: Implementation, Land. Adjudication